2013
DOI: 10.1152/japplphysiol.01144.2012
|View full text |Cite
|
Sign up to set email alerts
|

The role of trigeminal nasal TRPM8-expressing afferent neurons in the antitussive effects of menthol

Abstract: The cold-sensitive cation channel TRPM8 is a target for menthol, which is used routinely as a cough suppressant and as an additive to tobacco and food products. Given that cold temperatures and menthol activate neurons through gating of TRPM8, it is unclear how menthol actively suppresses cough. In this study we describe the antitussive effects of (-)-menthol in conscious and anesthetized guinea pigs. In anesthetized guinea pigs, cough evoked by citric acid applied topically to the tracheal mucosa was suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 53 publications
5
65
0
1
Order By: Relevance
“…The question as to how disease in the upper airway (largely innervated by the trigeminal nerve) can modulate the cough reflex, the afferent component of which is served by the vagus nerve, is not clear. It is possible that cough is due to mechanical stimulation of the laryngopharyngeal region by mucus, although, as already suggested, a more plausible explanation is that disease is not confined to the upper airway but that inflammation of the entire airway is present [78]. Most opinion leaders agreed with reservations that genetic studies are only useful in cough associated with neurological conditions.…”
Section: Question 15mentioning
confidence: 99%
“…The question as to how disease in the upper airway (largely innervated by the trigeminal nerve) can modulate the cough reflex, the afferent component of which is served by the vagus nerve, is not clear. It is possible that cough is due to mechanical stimulation of the laryngopharyngeal region by mucus, although, as already suggested, a more plausible explanation is that disease is not confined to the upper airway but that inflammation of the entire airway is present [78]. Most opinion leaders agreed with reservations that genetic studies are only useful in cough associated with neurological conditions.…”
Section: Question 15mentioning
confidence: 99%
“…Indeed, the menthol receptor TRPM8 is expressed in trigeminal ganglion neurons (McKemy et al, 2002) (Xing et al, 2008). Using a combination of functional and neurochemical (immunostaining and single-cell RT-PCR) studies, it was shown that menthol exerts its antitussive effect in the guinea pig by interacting at TRPM8-expressing (and TRPV1 negative) trigeminal afferents (Plevkova et al, 2013). Cough is believed to be "plastic": Up-and downregulation of the cough reflex may be mediated by distinct sensory afferents.…”
Section: +mentioning
confidence: 99%
“…In fact, TRPM8 is thought to be the target responsible for cough and bronchoconstriction caused by inhalation of cold air [86,87]. In contrast, menthol, which is thought to exert its actions through the TRPM8 channel, has been shown to inhibit citric acid-induced cough in guinea pigs [88,89] and humans [90] and causes a short-lasting decrease in capsaicin cough in normal subjects [91]. Furthermore, it has been used as an OTC medication for a number of years for its antitussive properties, and is often added to cigarettes to inhibit irritancy [73].…”
Section: Trpm8mentioning
confidence: 99%